PENERAPAN MODEL PEMBELAJARAN NOVICK BERBANTUAN MEDIA UNTUK MENINGKATKAN PEMAHAMAN TIK PADA SISWA SEKOLAH DASAR - Saj'dah, Isfa Rahadiani (2013)
The research was motivated by several issues including the rapid development of ICT so that the impact on the development of education.So the lesson using ICT is essential to be taught as a separate subject in elementary schools in order to improve the quality and educational purposes.However, in the field of ICT for teaching elementary school usually is limited to the teacher centre activities that students are lacking the ability to think properly chaneledTherefore, one of the learning model considered can help Increasing students' understanding of the learning model is Novick.The study was conducted to determine whether the application of learning models Novick can improve elementary school students' understanding of the ICT subjects.The research method used is the method by Quasi-Experimental graders sample VB and VC grade elementary school students Isola Bandung Pretest-Posttest design with Non-Equivalent Control Group Design. Instrument used in this study in the form of test (pretest and posttest) and observation sheet activities of teachers and students.Based on the overall analysis of the stages of the research found that: 1) Understanding students using Novick learning model is better than using a conventional teaching class, 2) Improved understanding of the students using learning model Novick higher than students using conventional learning, 3) student given treatment using multimedia-assisted learning model Novick overall increase understanding in ICT subjects Keywords: Model of Learning Novick